Crisis and Coloniality at Europe's Margins Creating Exotic Iceland - Loftsdóttir, Kristín (Routledge Research in Race and Ethnicity, 2019)
Crisis and Coloniality at Europe's Margins: Creating Exotic Iceland provides a fresh look at the current politics of identity in Europe, using a crisis at the margins of Europe to shed light on the continued embeddedness of coloniality in everyday aspirations and identities. Examining Iceland's response to its collapse into bankruptcy in 2008, the author explores the way in which the country sought to brand itself as an exotic tourist destination. With attention to the nation's aspirations, rooted in the late 19th century, of belonging as part of Europe, rather than being classified with colonized countries, the book examines the engagement with ideas of otherness across and within Europe, as European discourses continue to be based on racialized ideas of 'civilized' people. With its focus on coloniality at a time of crisis, this volume contributes to our understanding of how racism endures in the present and the significance of nationalistic sentiments in a world of precariousness. Anchored in part in personal narrative, this critical analysis of coloniality, racism, whiteness and national identities will appeal to scholars across the social sciences with interests in national identity-making, European politics and race in a world characterised by crisis.